Dendritic cell regulation of NK‐cell responses involves lymphotoxin‐α, IL‐12, and TGF‐β. Issue 6 (17th April 2015) - Sarhan, Dhifaf; Palma, Marzia; Mao, Yumeng; Adamson, Lars; Kiessling, Rolf; Mellstedt, Håkan; Österborg, Anders; Lundqvist, Andreas
<x xml:space="preserve">Abstract</x> Dendritic cell (DC) vaccines induce T‐cell responses in cancer patients. However, there is a paucity of data regarding the role of DC vaccines in shaping natural killer (NK) cell responses. Here, we observe that NK cells are less activated following DC vaccination. In vitro, DC‐mediated inhibition of NK cells did not require cell‐to‐cell contact, but required increased Signal transducer and activator of transcription 3 (STAT3) phosphorylation (pSTAT3) in DCs. When phosphorylation of STAT3 was inhibited in DCs, we found that DCs did not suppress NK cells, and observed an increase in the production of lymphotoxin‐alpha (LTα) and interleukin‐12 (IL‐12) as well as reduced release of transforming growth factor beta (TGF‐β). The addition of recombinant LTα or IL‐12 to the DC‐NK‐cell cocultures restored NK‐cell activity, and neutralization of TGF‐β resulted in elevated production of LTα and IL‐12 from DCs. Compared with LPS, DCs matured with a cocktail of R848, poly I:C, and IFN‐γ showed reduced levels of pSTAT3 and higher levels of LTα and IL‐12 and did not inhibit NK‐cell activity. These results show that LTα, IL‐12, and TGF‐β are involved in the cross‐talk between NK cells and DCs. Our findings have important implications for the development of DC‐based vaccination strategies to potentiate NK‐cell responses in patients with cancer.